Prevalence of metabolic syndrome in women with polycystic ovarian syndrome: an observational study in a tertiary care centre in Pondicherry, India - N. R., Indu; P. B., Hiremath; Sanyal, Urmi; ., Shilpa; ., Rohini; Hiremath, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Polycystic Ovarian Syndrome (PCOS) is a multifactorial, polygenic and multisystem endocrine disorder affecting women in reproductive age. PCOS diagnosis is based on 2003 Rotterdam criteria It has been noted that hyperinsulinemia is a central factor in the pathogenesis of PCOS. Many studies show evidence of a critical link between PCOS and Metabolic Syndrome (MBS). Methods: It was a hospital - based observational study done over a period of one year with a sample size of 177.An observational study was done in patients satisfying the inclusion and exclusion criteria. After taking informed and written consent, history was obtained from the patient to know the age, socioeconomic status, present and past clinical history, menstrual and obstetric history, personal and family history and any other history as deemed necessary. Patient was clinically assessed to know the height, weight, body mass index. Results: The prevalence of MBS was 37.2%. The commonest age group was between 25- 35 years.There is no statistical association between educational qualification, economic status and the prevalence of MBS and There no significant association between the presence of acne, androgenic aloepecia and the presence of PCOS.While the presence of increased waist circumference > 88cms, USG findings consistent with PCOS, high blood pressure > 130/85 mm of Hg, elevated FBS > 110 mg/dl, low HDL <50 mg/dl were statistically significant. Conclusions: The results can be used to formulate a screening policy for metabolic syndrome, particularly in the low resource settings of developing countries.